Determinants of community pharmacists' information gathering and counseling practices during the management of minor ailments - Ahmed Mohamed Makhlouf; Mohamed Izham Mohamed Ibrahim; Ahmed Awaisu; Saseendran Kattezhathu Vyas; Kazeem Babatunde Yusuff (Elsevier, 2021)
Objective: To assess the determinants of community pharmacists' information gathering and counseling practices during the management of minor ailments in Qatar. Method: A cross-sectional study of 305 community pharmacists was conducted with a pre-tested 27-item questionnaire. Bivariate logistic regression was used to identify the determinants of information gathering and counseling practices. Results: The response rate was 92.5% (282/305). A majority of the respondents (68.1%) were males, within the age range of 31-40 years (55.3%), work for chains pharmacies (77.3%), and were predominantly of foreign nationalities (94.7%). Patients' identity (91.1%), age (92.2%), symptoms (92.6%) and duration of symptoms (89.3%) were most frequent information gathered, while dose (99%), frequency (97.8%), route of administration (95.7%), and duration of use (92.9%) were the most frequent counseling information. Median information gathering score was significantly higher in females and among community pharmacists in chain pharmacies (p < 0.05), while median counseling practice scores were significantly higher among in chain pharmacies (p < 0.05). Consultation time of 6-10 min (OR = 1.75, 95% CI: 1.02-3.0, p = 0.04) and female gender (OR = 2.10, 95% CI: 1.16-3.79, p = 0.01) were significant determinants of information gathering, while age group (31-40 years) (OR = 1.84, 95% CI: 1.05-3.22, p = 0.03) and consultation time (6-10 min) (OR = 2.24, 95% CI: 1.31-3.86, p = 0.003) were significant determinants of counseling practices. Conclusion: The significant determinants of community pharmacists' Information gathering and counseling practices during the management of minor ailments were female gender and consultation time (6-10 min), and age group (31-40 years) and consultation time (6-10 min) respectively.